Counter Women Trafficking Commission (CWTC): Fighters for Justice for Migrants and Human Trafficking - Kwirinus, Dismas; Emanuel, Fransiskus; Angga, Stepanus; Mayolla, Innoccentius Gerardo; Peri, Heribertus (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
The focus of this article is to examine the Counter Women Trafficking Commission (CWTC): Fighters for Justice for Migrants and Human Trafficking. Migrants are people who are vulnerable to physical and psychological violence. They work abroad to change their fortunes for the better but that goal sometimes doesn't match their expectations. Instead, they often experience injustice and are treated inhumanely by their employers. This situation certainly concerns us all. In this case, CWTC or Talitha Kum as an organization that is present and as a face of hope for small people trying to fight for justice for migrants and victims of human trafficking. So in this study, we will utilize qualitative research methods. We conducted interviews with the head of CWTC or Talitha Kum Malang Raya and looked for data on migrants and how these organizations provide services to migrants. Then, after the data was collected, we used the content analysis method to analyze the research data. This analysis will produce research findings that become a construct in viewing the contextual development of CWTC. The discussion of these findings will become an actual study in interpreting justice for the underprivileged.